White Freedom : The Racial History of an Idea - Stovall, Tyler Edward (Book collections on Project MUSE., 2021)
"The era of the Enlightenment, which gave rise to our modern conceptions of freedom and democracy, was also the height of the trans-Atlantic slave trade. America, a nation founded on the principle of liberty, is also a nation built on African slavery, Native American genocide, and systematic racial discrimination. White Freedom traces the complex relationship between freedom and race from the eighteenth century to today, revealing how being free has meant being white. Tyler Stovall explores the intertwined histories of racism and freedom in France and the United States, the two leading nations that have claimed liberty as the heart of their national identities. He explores how French and American thinkers defined freedom in racial terms and conceived of liberty as an aspect and privilege of whiteness. He discusses how the Statue of Liberty-a gift from France to the United States and perhaps the most famous symbol of freedom on Earth-promised both freedom and whiteness to European immigrants. Taking readers from the Age of Revolution to today, Stovall challenges the notion that racism is somehow a paradox or contradiction within the democratic tradition, demonstrating how white identity is intrinsic to Western ideas about liberty. Throughout the history of modern Western liberal democracy, freedom has long been white freedom. A major work of scholarship that is certain to draw a wide readership and transform contemporary debates, White Freedom provides vital new perspectives on the inherent racism behind our most cherished beliefs about freedom, liberty, and human rights"--